Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Semangat Kerja Karyawan Pada Masa Pandemi Covid-19 (Study pada karyawan gudang UD. SINAR REJEKI Surabaya) - Santirianingrum Soebandi; Mefia Fera Agustina (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2021)
This research is an empirical study at UD SINAR REJEKI Business Entity in Surabaya which aims to prove that Compensation and Work Environment have a significant influence on employee morale. This study used a quantitative approach with a population of 57 people in the UD SINAR REJEKI business entity and a sample of 40 respondents. The analysis technique used is multiple linear regression using SPSS 20 software preceded by data quality test and classic assumption test. The results showed that all data were declared valid and reliabel and met the classical assumption test requirements. The conclusion of the study that compensation and work environment had a significant effect on the work spirit of employees with evidence of t-test results on both variables obtained a significance value of less than 0.05.